Desafios e perspectivas referentes ao letramento acadêmico na transição do ensino médio para o ensino superior: percepções de alunos ingressantes no campus da UFPA em Bragança - SANTOS, Adriane Reis da Silva (2024)
Entering university is marked by several challenges, leading first-year students to experience moments of apprehension, as the transition between High School and Higher Education requires cultural and intellectual changes for which they are often unprepared. In this perspective, this paper aims to identify the challenges and perspectives faced by first-year students at Universidade Federal do Pará - Bragança Campus concerning academic literacy, and understanding which factors affect this first contact with Higher Education. The study was conducted through the analysis of two questionnaires applied to students of the various undergraduate courses on the Campus, after two short courses in the area of Language, offered by the “Leveling Learning Program: Language, Exact Sciences and Natural Sciences areas” for first-year students at Bragança Campus, during the period between the years 2020 and 2023. The theoretical bases for this study were the contributions of some scholars, such as Carlino (2017), Coulon (2017), Ferreira and Lousada (2016), Oliveira and Araújo (2017), and Pinho et. al (2015), among others. The methodological approach was descriptive research, with a qualitative nature. The results imply two main factors in the transition of students from High School to Higher Education: the first one is internal and is related to the teacher/student rapport and the format of curricular courses offering organization, adopted by the several departments; the second one is external and is related to outdated Basic Education and the consequences of the pandemic of the coronavirus, which causes Covid-19.